2021
DOI: 10.3390/ijms22126435
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Prefibrillar Oligomers: The Surprising Commonalities in Their Structure and Activity

Abstract: It has been proposed that a “common core” of pathologic pathways exists for the large family of amyloid-associated neurodegenerations, including Alzheimer’s, Parkinson’s, type II diabetes and Creutzfeldt–Jacob’s Disease. Aggregates of the involved proteins, independently from their primary sequence, induced neuron membrane permeabilization able to trigger an abnormal Ca2+ influx leading to synaptotoxicity, resulting in reduced expression of synaptic proteins and impaired synaptic transmission. Emerging evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 204 publications
(286 reference statements)
0
10
0
Order By: Relevance
“…Brain adaptations to WBV could also involve multiple brain regions in humans, given the close communication between the sensory systems of vibration perception and the areas that oversee cognitive functions [ 33 ]. In this regard, Regterschot et al investigated the acute effects of passive WBV on executive functions in 133 healthy young adults subjected to six training sessions (frequency 30 Hz, amplitude approximately 0.5 mm) alternating with six rest sessions of two minutes each.…”
Section: Physiological Adaptations To Wbvmentioning
confidence: 99%
“…Brain adaptations to WBV could also involve multiple brain regions in humans, given the close communication between the sensory systems of vibration perception and the areas that oversee cognitive functions [ 33 ]. In this regard, Regterschot et al investigated the acute effects of passive WBV on executive functions in 133 healthy young adults subjected to six training sessions (frequency 30 Hz, amplitude approximately 0.5 mm) alternating with six rest sessions of two minutes each.…”
Section: Physiological Adaptations To Wbvmentioning
confidence: 99%
“…However, this finding does not apply to all of IDE’s substrates. The self-assembly of IDE’s amyloidogenic substrates has been shown to be enhanced by anionic lipids in membranes. ,,, Zhang et al showed that even low levels of anionic lipids promote the aggregation of cationic IAPP and facilitate IAPP-induced leakage of membranes . Clusters of anionic GM1 gangliosides in membranes accelerate Aβ aggregation to form assemblies with increased cytotoxicity .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a misfolding event has been proposed as the underlying mechanism that involves the assumption by a specific protein of an incorrect conformation. This initial event causes the misfolded proteins to aggregate into increasingly large species with a high neurotoxic potential, leading to progressive neuronal loss in certain brain areas [ 79 ].…”
Section: Physical Exercise As a Non-pharmacological Strategy To Preve...mentioning
confidence: 99%